A qualitative investigation of lay and professional perspectives of community pharmacy extended palliative care services - Ali, Abid (2021)
In the UK, an increasingly ageing population has expanded the patient population affected by multiple morbidities and palliative care needs. Patients report having complicated medicine regimens, a high incidence of problematic polypharmacy, and significant medication management problems. Growing numbers of patients opting for home-based palliative care, and in the absence of adequate support, they are faced with an increased burden of care. Furthermore, family caregivers accept this burden without formal training or regular outside support. As a result, patients and family caregivers have considerable unmet pharmaceutical needs. This environment presents an urgent need to explore the potential for community pharmacists, who traditionally have had limited involvement, to help support patients, family caregivers and existing palliative care services.